2019
DOI: 10.1161/circep.118.006835
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront Field Mapping Reveals a Physiologic Network Between Drivers Where Ablation Terminates Atrial Fibrillation

Abstract: Background: Localized drivers are proposed mechanisms for persistent atrial fibrillation (AF) from optical mapping of human atria and clinical studies of AF, yet are controversial because drivers fluctuate and ablating them may not terminate AF. We used wavefront field mapping to test the hypothesis that AF drivers, if concurrent, may interact to produce fluctuating areas of control to explain their appearance/disappearance and acute impact of ablation. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The exact type of organization is a topic of controversy, as some groups have proposed that AF is maintained via dissociated endo-epicardial breakthroughs (de Groot et al, 2010) or focal or rotational drivers (Jalife, 2003;Baykaner et al, 2014;Haissaguerre et al, 2014;Lalani et al, 2014;Schricker et al, 2014;Hansen et al, 2015Hansen et al, , 2017Hansen et al, , 2018Quintanilla et al, 2016;Zahid et al, 2016;Csepe et al, 2017;Nattel et al, 2017;Zhao et al, 2017). Recent seminal work has demonstrated that rotational and focal drivers exist at sites that terminate AF when ablated, reinforcing the role of organized drivers maintain (Zhao et al, 2017;Kowalewski et al, 2018;Zaman et al, 2018;Leef et al, 2019).…”
Section: Electrical Substratementioning
confidence: 99%
See 2 more Smart Citations
“…The exact type of organization is a topic of controversy, as some groups have proposed that AF is maintained via dissociated endo-epicardial breakthroughs (de Groot et al, 2010) or focal or rotational drivers (Jalife, 2003;Baykaner et al, 2014;Haissaguerre et al, 2014;Lalani et al, 2014;Schricker et al, 2014;Hansen et al, 2015Hansen et al, , 2017Hansen et al, , 2018Quintanilla et al, 2016;Zahid et al, 2016;Csepe et al, 2017;Nattel et al, 2017;Zhao et al, 2017). Recent seminal work has demonstrated that rotational and focal drivers exist at sites that terminate AF when ablated, reinforcing the role of organized drivers maintain (Zhao et al, 2017;Kowalewski et al, 2018;Zaman et al, 2018;Leef et al, 2019).…”
Section: Electrical Substratementioning
confidence: 99%
“…A promising technique was recently proposed using wavefront field mapping (Leef et al, 2019) to reveal organized areas of control during AF (Figures 9A,B). This novel vector mapping method computes activation times to calculate phase ( Figure 9C), activation fronts, and gradient matching to display the vector fields ( Figures 9D-F) to describe propagation of these fronts.…”
Section: Wavefront Field Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…By testing for causal relationships of electrical signals between neighboring regions of the heart over time and quantifying the number of causal relationships above a set “causality threshold,” we can reliably measure global fibrillation organization and characterize the AF electrophenotype, even when applied to low spatial resolution clinical AF data ( Figure 2 ). Other novel analysis approaches, such as wavefront field mapping, which can reveal the network of rotational and focal sites in AF ( Leef et al, 2019 ), electrocardiographic flow mapping, which determines the main propagation patterns during AF ( Bellmann et al, 2019 ), or mapping of connectivity between different regions of the atria usual mutual information analysis ( Tao et al, 2017 ), may also be able to identify the AF electrophenotype to guide mechanism-directed treatments.…”
Section: Mechanism-directed Treatment Based On Af Electrophenotypementioning
confidence: 99%
“…ECGi also focuses on short periods between QRS complexes (1228 ± 56 ms) which inherently limits the stability of any identified feature, and the use of adenosine may alter AF 21 . Further analysis should ultimately extend beyond phase singularities and current studies are examining whether the spatial areas of organized features 22 or their rate 9 may indicate a hierarchy of relatively more or less important sites to AF.…”
mentioning
confidence: 99%